Post-earning announcement drift and value-glamour anomalies in NSE listed firms - Pankaj Kumar Gupta; Devendra Kumar Dhusia (Trends Economics and Management, 2021)
Purpose of the article: Of the various market anomalies, the Value-Glamour anomaly and Post-Earnings Announcement Drifts (PEAD) have consistently attracted the attention of researchers. Prior studies have established that the reaction of value stocks and glamour stocks to the earnings announcement differs significantly and there is a close relationship between the PEAD and abnormal returns arising due to earning announcement surprises. We have studied the drift patterns of various value and glamour portfolios and tested whether the direction of the earnings announcement abnormal return is opposite to that of earnings surprise in the Indian market. Methodology: We use the statistics of 100 firms listed on the NSE for a sample period of 2014-2018. We use a set of 1130 observations analysed using the expectations formation approach around earnings and evaluate the post earnings announcement drift. We use the Earnings Response Coefficients to find the association between abnormal stock returns and earnings surprises. Scientific aim: The aim of this research is to improve the knowledge of market anomalies in developing markets such as India focusing on the impact of earnings announcement on growth and value stocks. Findings: We find that a negative association of abnormal stock returns with surprise in accounting earnings announcements. The stocks, which are overvalued or undervalued, are properly priced after the earnings announcements. Our results refute the earlier studies evidencing the strong support in favour of market inefficiency in the Indian context, particularly with respect to publicly available earnings information. Conclusions: The Indian stock market tends to be efficient with respect to earnings announcements and therefore does not produce excessive returns. However, a heterogeneity with respect to earnings announcement may exist among the category of stocks depending upon liquidity position. Superior returns cannot be derived by traders and investors on a consistent basis from value-glamour anomaly.
Keywords: C22; G14; G32; 650; post-earnings announcement drifts; abnormal returns; value and glamour anomaly; earnings response coefficient